2019
DOI: 10.1016/j.ifset.2018.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Electrospraying assisted by pressurized gas as an innovative high-throughput process for the microencapsulation and stabilization of docosahexaenoic acid-enriched fish oil in zein prolamine

Abstract: Electrospraying assisted by pressurized gas as an innovative high-throughput process for the microencapsulation and stabilization of docosahexaenoic acid-enriched fish oil in zein prolamine. Innovative Food Science & Emerging Technologies. 51:12-19.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
48
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 48 publications
(82 reference statements)
2
48
0
Order By: Relevance
“…(Valencia, Spain). This proprietary pilot installation by Bioinicia comprises an injection unit, a drying chamber, and a cyclonic collector as described elsewhere [5]. The experiments were optimally performed bubbling continuously nitrogen into the emulsion at controlled ambient conditions, i.e., 25 • C and 30% relative humidity (RH), which was then pumped at 1 mL/min into the injector that worked with an assisted air pressure of 10 L/min and a variable electric voltage from 0 to 30 kV.…”
Section: Eapg Processmentioning
confidence: 99%
See 3 more Smart Citations
“…(Valencia, Spain). This proprietary pilot installation by Bioinicia comprises an injection unit, a drying chamber, and a cyclonic collector as described elsewhere [5]. The experiments were optimally performed bubbling continuously nitrogen into the emulsion at controlled ambient conditions, i.e., 25 • C and 30% relative humidity (RH), which was then pumped at 1 mL/min into the injector that worked with an assisted air pressure of 10 L/min and a variable electric voltage from 0 to 30 kV.…”
Section: Eapg Processmentioning
confidence: 99%
“…They are mainly found in marine products such as fish, algae and krill oils [1]. It is really common the use of fish oils as a source of omega-3 fatty acids; however fish oil present certain disadvantages, since fish oil impart their typical fishy flavor when directly added to foods, can be contaminated with methyl mercury, and over-fishing causes a burden on natural fish populations [5]. The use of algae and krill oils, which are the primary source of PUFAs, present the advantage of the absence of pollutants as well as the lack of unpleasant odor [6,7].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have reported the encapsulation of omega-3 PUFAs by electrospraying Busolo, Torres-Giner, Prieto, & Lagaron, 2018). Recently, we have reported the potential of dextran and glucose syrup as main biopolymers (in combination with whey protein and pullulan) for the production of fish oil-loaded electrosprayed capsules .…”
Section: Introductionmentioning
confidence: 99%